The Role of Organizational Communication in Improving Work Team Effectiveness - Ridwansyah Arifandi Arifandi; Winda Aidin; Nurul Mupida Lubis; Afwan Syahril Manurung (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2024)
Organizational communication is essential to ensure that teams work well in the workplace. In this article, organizational communication is discussed as a tool to ensure effective coordination, information sharing, and team conflict resolution. Organizations can increase productivity, build strong interpersonal relationships, and create a harmonious work environment by using various communication methods, including vertical, horizontal, and diagonal methods. In addition, this article identifies components that influence communication effectiveness, such as interpersonal skills, technology, work culture, and organizational structure. To improve the quality of team communication, methods such as communication training, use of appropriate media, and structured feedback are suggested. Work teams can communicate better, achieve common goals, and handle problems better.